The Efficiency Costs of Dividend Taxation with Managerial Firms - Marko Köthenbürger; Michael Stimmelmayr (Center for Economic Studies and ifo Institute (CESifo), 2015)
The paper analyzes the efficiency costs of dividend taxation in an effort-based corporate agency model in which non-verifiable managerial effort enhances taxable profits. We show that investment changes following a rise in dividend taxes might not be sufficient to infer the efficiency cost of dividend taxation as well as the financing regime of the firm that underlies the investment response, in contrast to insights from previous literature. We provide a testable implication to infer the mode of investment finance from investment responses. Furthermore, we show that imposing income tax on managerial incentive pay is welfare equivalent to a general dividend tax. Finally, we relate the results to recent empirical findings in the literature on dividend taxation.
Keywords: H25; D21; 330; dividend taxation; managerial effort; corporate governance; tax on incentive pay; managerial firms